2011
DOI: 10.1007/s10646-011-0707-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mRNA expression of DMRT93B, vitellogenin, and cuticle 12 in Daphnia magna and their biomarker potential for endocrine disruption

Abstract: We explored the use of molecular genetic biomarkers for endocrine disruption in Daphnia magna after the exposure to fenoxycarb (FOC), a model juvenile hormone analog. For this purpose, the mRNA expression patterns of DMRT93B (DMRT, sex determination), cuticle 12 (CUT, molting), and vitellogenin (VTG, embryo development) were determined in D. magna. Furthermore, these results were compared with developmental abnormality and reproduction performance. The fold changes of CUT and VTG mRNA expression showed signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…Thus, Cutie is likely to be highly expressed in animals that have a higher demand but lower availability of Ca 2+ . Our result are consistent with previous studies that demonstrated differential expression of genes involved in molting, such as cuticle proteins and proteolytic enzymes, under other environmental stressors such as fungicides and metals (Soetaert et al 2007;Vandenbrouck et al 2009;Kim et al 2011). …”
Section: Cuticle Proteins: Cutie and Icp2supporting
confidence: 93%
“…Thus, Cutie is likely to be highly expressed in animals that have a higher demand but lower availability of Ca 2+ . Our result are consistent with previous studies that demonstrated differential expression of genes involved in molting, such as cuticle proteins and proteolytic enzymes, under other environmental stressors such as fungicides and metals (Soetaert et al 2007;Vandenbrouck et al 2009;Kim et al 2011). …”
Section: Cuticle Proteins: Cutie and Icp2supporting
confidence: 93%
“…These two proteins are functionally related to reproduction and development [25]. Both miconazole and promethazine are known to target the calcium-binding CaM [17], [19], a highly conserved protein that in D .…”
Section: Discussionmentioning
confidence: 99%
“…Biosystems, Foster, CA, USA) in a 20 µL reaction volume according to the protocol recommended by the manufacturer. The primers for a 77 bp fragment of vitellogenin (GenBank accession number: DY037239; forward: 5′-GCGGACGAGGTTGCAAAG-3′ and reverse: 5′-AGGAGCAGGAAGATGTCGTTCT-3′), a 199 bp fragment for cuticle protein 12 (DW985490; forward: 5′-AGCCAGTGGAACTACG-3′ and reverse: 5′-TCCAGCATCATCAGCG-3′), and a 71 bp fragment for β-actin (AJ292554; forward: 5′-CCACACTGTCCCCATTTATGAAG-3′ and reverse: 5′-CGCGACCAGCCAAATCC-3′) were adopted from Soetaert et al [26] and Kim et al [25]. The reaction plate was subjected in StepOne (Applied BioSystems) real time PCR with reverse transcription.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations